Does what you study at age 14–16 matter for educational transitions post-16?. (2nd January 2018) - Moulton, Vanessa; Sullivan, Alice; Henderson, Morag; Anders, Jake
Abstract: This paper considers whether subject choice at 14–16 influences post-16 transitions, taking into account prior academic attainment and school characteristics, and if so, whether this accounts for socioeconomic, gender, and ethnic differences in access to post-16 education. We consider post-16 progression to full-time education, A-levels, and studying two or more facilitating subjects at A-level. We use 'Next Steps', a study of 16, 000 people born in England in 1989–1990, linked to administrative education records (the National Pupil Database). We find that students pursuing an EBacc-eligible curriculum at 14–16 had a greater probability of progression to all post-16 educational outcomes, while the reverse was true for students taking an applied GCSE subject. Curriculum differences did not explain the social class differences in post-16 progression, but an academic curriculum was equally valuable for working-class as for middle-class pupils. Pursuing an EBacc-eligible curriculum particularly strongly increased the chances of girls and white young people staying in the educational pipeline, whereas applied subjects were particularly detrimental for girls. An EBacc-eligible curriculum at age 14–16 increased the chances of studying subjects preferred by Russell Group universities at A-level.